2021
DOI: 10.1037/emo0000750
|View full text |Cite
|
Sign up to set email alerts
|

Valuing emotional control in social anxiety disorder: A multimethod study of emotion beliefs and emotion regulation.

Abstract: This study examines relationships between emotion beliefs and emotion regulation strategy use among people with social anxiety disorder (SAD) and a psychologically healthy control group. Using experience-sampling methodology, we tested group differences in 2 types of emotion beliefs (emotion control values and emotion malleability beliefs) and whether emotion beliefs predicted trait and daily use of cognitive reappraisal and emotion suppression. People with SAD endorsed higher emotion control values and lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 110 publications
2
19
0
Order By: Relevance
“…Beliefs about emotion and emotion regulation, or "emotion beliefs" (Ford & Gross, 2019, p. 74), appear to be important for acute outcomes (e.g., emotional experiences), and chronic cumulative outcomes (e.g., well-being; Ford & Gross, 2019). Negative emotion beliefs are a key criterion defining emotional disorders (Bullis et al, 2019), but empirical research lags (Goodman et al, 2020). Two emotion beliefs that are garnering growing interest are, (a) whether emotions are good or bad ("goodness"), and (b) whether emotions are controllable or uncontrollable ("controllability"); neither capture the S-R and C-M viewpoints at the centre of the current paper.…”
Section: Emotion Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beliefs about emotion and emotion regulation, or "emotion beliefs" (Ford & Gross, 2019, p. 74), appear to be important for acute outcomes (e.g., emotional experiences), and chronic cumulative outcomes (e.g., well-being; Ford & Gross, 2019). Negative emotion beliefs are a key criterion defining emotional disorders (Bullis et al, 2019), but empirical research lags (Goodman et al, 2020). Two emotion beliefs that are garnering growing interest are, (a) whether emotions are good or bad ("goodness"), and (b) whether emotions are controllable or uncontrollable ("controllability"); neither capture the S-R and C-M viewpoints at the centre of the current paper.…”
Section: Emotion Beliefsmentioning
confidence: 99%
“…Extending the area of emotion beliefs beyond the emergent concepts of goodness and controllability is important for emotion science Tamir et al, 2007), because people's active attempts to manage their emotions might be in part predicated on their beliefs about how emotions occur and how they can be managed (Ford & Gross, 2019). The proposed S-R and C-M beliefs might be important for emotion regulation, because such superordinate emotion beliefs precede emotion regulation attempts (Trincas et al, 2016), and influence the occurrence and effectiveness of emotion regulation attempts (Goodman et al, 2020). For example, a belief that cognitive change cannot yield emotion change, may result in premature stopping of emotion-regulation efforts (Sheppes et al, 2015).…”
Section: Emotion Beliefsmentioning
confidence: 99%
“…Incremental ITEs are also linked to the suppression of emotions [46]. Interestingly, incremental theories of emotions are important for the adoption of emotional control and suppression strategies, but they are not related to cognitive overestimation [47].…”
Section: Implicit Theories Of Emotionsmentioning
confidence: 99%
“…Generally, aerobic exercises are more effective in decreasing the stress level (Akyol & Imamoğlu, 2018). In the last years, a lot of research has been done to control and manage the feeling of people (Goodman, Kashdan, & İmamoğlu, 2020). In a study by Yamaner, Cplak, and Imamoğlu (2020) found sports education has a positive effect on university students' optimal performance.…”
Section: Introductionmentioning
confidence: 99%